AN ATTRIBUTE STUDY OF DEFICIENCIES IN SUPPLY CHAIN MANAGEMENT: A CASE OF CONSTRUCTION INDUSTRY - Rafique Rehman Panhwar , Shabir Hussain Khahro , Nafees Ahmed Memon , Parvez Ahmed Shaikh , Qasim Hussain Khahro (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Globally, Construction Industry contributes its pivotal role in the improvement of all domains of life. In recent decades, Supply Chain (SC) has had a gigantic impact in the arena of Construction Engineering (CE). It covers the management of materials from mobilization to decommission phase of the projects. The competitive global demand varies from time to time from producer to customer. Many types of research have been carried out in the field of Supply Chain Management (SCM). With time there is a need for the improvement of factors which are causing hindrances/deficiencies in the performance level of SCM in building construction sector. Hence, this study aims to investigate the factors which cause a delay in the performance level in SCM construction industry. After a comprehensive literature review, factors are identified. They are then validated by unstructured interviews from experts working in the field of the construction industry. A total of 110 questionnaires were sent to respondents, 79 were received from succeeded respondents. The collected data were analyzed through SPSS software and Average Index weight were calculated for ranking. The outcome of this study will help improve the performance level in supply chain management in building construction sector practices in construction projects.